2014
DOI: 10.1097/iio.0000000000000047
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Proteomic Pathophysiology of Pseudoexfoliation Glaucoma

Abstract: PEX stems from a pathologic elastotic process involving the cross-linking gene lysyl oxidase-like-1 (LOXL1), and is associated with abnormal formation of elastic extracellular matrix. We previously described a protein sink model to explain PEX material deposition on the lens capsule and other intraocular surfaces. Recent research findings not only provide evidence to support this hypothesis, but also further our understanding of the fundamental disease process. A key aspect of the pathogenic process is the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 58 publications
(81 reference statements)
0
34
0
Order By: Relevance
“…The prevalence of PXF varies widely across the globe ranging from 0% in Eskimos, 1–2% in the United States, 5% in Turkish population to >25% in Scandinavian countries and Navajo Indians and between males and females. [ 1 , 5 , 6 , 13 , 14 , 27 29 ] Some postulated reasons included differences in environment, diet and lifestyle, differences in hours of outdoor exposure and distance from equator apart from basic difference in genetic susceptibility study design and lack of using slit lamp under dilated examination in many studies. In the Reykjavik Eye Study, prevalence increased from 2.5% in those aged 50–59 years to 40.6% in those aged≥ 80 years.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PXF varies widely across the globe ranging from 0% in Eskimos, 1–2% in the United States, 5% in Turkish population to >25% in Scandinavian countries and Navajo Indians and between males and females. [ 1 , 5 , 6 , 13 , 14 , 27 29 ] Some postulated reasons included differences in environment, diet and lifestyle, differences in hours of outdoor exposure and distance from equator apart from basic difference in genetic susceptibility study design and lack of using slit lamp under dilated examination in many studies. In the Reykjavik Eye Study, prevalence increased from 2.5% in those aged 50–59 years to 40.6% in those aged≥ 80 years.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, PXG is a severe form of open-angle glaucoma associated with worse prognosis. PXG is characterized by the abnormal deposition of pseudoexfoliative material (fibrillar extracellular matrix (ECM)) in the anterior segment of the eye causing the obstruction [35]. It is difficult to elucidate the precise mechanism(s) by which the variant rs12997 in ACVR1 may influence the risk of these glaucoma types.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al recently identified the LOX mutation that causes familial TAAD: the Ser280Arg mutation produced a less active variant that led to disorganised elastic fibres and increased collagen in patients’ aortas [127]. Several reports have described an association between LOXL1 and glaucoma, specifically in the early stages of the elastic fibre disorder exfoliation syndrome (XFS) [76,[128], [129], [130], [131]]. LOXL1 colocalised with elastin, fibrillin-1 and fibulin-4, which were also upregulated, and its expression was enhanced by TGFβ1 and other XFS-associated stimuli in Tenon’s capsule fibroblasts [76].…”
Section: Functional Modifiers Of Elastic Fibresmentioning
confidence: 99%